The plasma membrane of Saccharomyces cerevisiae: structure, function, and biogenesis. - van der Rest, M E (1995)
The composition of phospholipids, sphingolipids, and sterols in the plasma membrane has a strong influence on the activity of the proteins associated or embedded in the lipid bilayer. Since most lipid-synthesizing enzymes in Saccharomyces cerevisiae are located in intracellular organelles, an extensive flux of lipids from these organelles to the plasma membrane is required. Although the pathway of protein traffic to the plasma membrane is similar to that of most of the lipids, the bulk flow of lipids is separate from vesicle-mediated protein transport. Recent advances in the analysis of membrane budding and membrane fusion indicate that the mechanisms of protein transport from the endoplasmic reticulum to the Golgi and from the Golgi to plasma membrane are similar. The majority of plasma membrane proteins transport solutes across the membrane. A number of ATP-dependent export systems have been detected that couple the hydrolysis of ATP to transport of molecules out of the cell. The hydrolysis of ATP by the plasma membrane H(+)-ATPase generates a proton motive force which is used to drive secondary transport processes. In S. cerevisiae, many substrates are transported by more than one system. Transport of monosaccharide is catalyzed by uniport systems, while transport of disaccharides, amino acids, and nucleosides is mediated by proton symport systems. Transport activity can be regulated at the level of transcription, e.g., induction and (catabolite) repression, but transport proteins can also be affected posttranslationally by a process termed catabolite inactivation. Catabolite inactivation is triggered by the addition of fermentable sugars, intracellular acidification, stress conditions, and/or nitrogen starvation. Phosphorylation and/or ubiquitination of the transport proteins has been proposed as an initial step in the controlled inactivation and degradation of the target enzyme. The use of artificial membranes, like secretory vesicles and plasma membranes fused with proteoliposomes, as model systems for studies on the mechanism and regulation of transport is evaluated.